HUBUNGAN AKTIVITAS FISIK DENGAN KADAR ASAM URAT DARAH PADA ORANG LANJUT USIA DI PUSKESMAS PADANG KANDIS KABUPATEN LIMA PULUH KOTA - Salsabilla, Ainna Fajra; Irramah, Miftah; Lestari, Yuniar (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Uric acid is a crystalline acid, the end product of purine metabolism. Normal uric acid levels depend on age and gender, exceeding the normal limit indicates an increase in uric acid levels. One contributing factor to elevated uric acid is increased physical activity. This study aims to determine the Relationship between Physical Activity and Uric Acid Levels in elderly people at the Padang Kandis Health Center, Lima Puluh Kota Regency. This observational analytic study, with a cross sectional research design and includes 30 elderly participants meeting inclusion and exclusion criteria, assessed through the Global Physical Activity Questionare (GPAQ). Uric acid levels were measured using Autocheck digital instruments and test strips. Data analysis utilized the Chi-Square Test. Results revealed an equal ratio of normal and high uric acid levels in the elderly (50%), and the highest level of physical activity was light physical activity (46,6%). High uric acid levels were found more in the elderly with low physical activity levels (46,3%). The Chi-Square Test yielded  p=0,208 (>0,05).This study found no significant relationship between physical activity and uric acid levels in elderly people at the Padang Kandis Health Center, Lima Puluh Kota Regency.